NFTs, DAOs AND SMART CONTRACTS: WHERE IS THE DECENTRALISATION? - Ciantar, Marica (International Journal of Law in Changing World, 2023)
DAOs, decentralised autonomous organisations, you have the power, right? Well, like most other matters now-a-days, it depends. Oftentimes, the relationship between NFTs and DAOs is intertwined as a DAO may be set up with the purpose of creating NFTs or else, one may buy an NFT to become a DAO member. Both DAOs and NFTs make use of smart contracts on a blockchain therefore, for this paper it is essential to speak about such. However, the main purpose of this paper is to answer the following questions, • How decentralised is a DAO? • What is the role of NFTs within a DAO? • How can NFTs enhance the workings of a truly decentralised autonomous organisation? Such questions will be answered by first delving into an introduction to smart contracts, NFTs and DAOs and a discussion on how they interact then the focus will shift more on the decentralisation within a DAO. This author believes that decentralisation should stop being used as a hype word in the blockchain sphere thus there will also be a discussion on certain problems when it comes to centralised and decentralised points in a DAO, whether such are realised or not. Reference will be made to cases and hacks within the blockchain sphere to show that a DAO is not necessarily decentralised and in turn, your NFT is not necessarily safe. With regards law, the author will focus on both the Maltese Innovative Technology Arrangement and Services Act and the Wyoming Decentralized Autonomous Organizations Supplement as both these laws directly regulate DAOs and in turn serve as a means to protect the member and the client of the DAO, and their NFTs.